Disability, work, and cash benefits - Mashaw, Jerry L.; National Academy of Social Insurance (U.S.); National Institute on Disability and Rehabilitation Research (U.S.) (Kalamazoo, Mich. : W.E. Upjohn Institute for Employment Research, 1996)
Reviews the US Social Security disability programme, with a view to determining whether rehabilitation and work could be incorporated in the income programme without greatly expanding costs or weakening the right to benefit for disabled persons.
Lessons from the vocational rehabilitation/Social Security Administration experience / Edward Berkowitz, David Dean -- Disability and work : lessons from the private sector / H. Allan Hunt, Rochelle V. Habeck, Patricia Owens, David Vandergoot -- Quantitative outcomes of the transitional employment training demonstration : summary of net impacts / Aaron J. Prero -- Policies for people with disabilities in U.S. employment and training programs / Burt S. Barnow -- Improving the return to work of social security disability beneficiaries / Monroe Berkowitz -- People with disabilities : access to health care and related benefits / Robert F. Friedland, Alison Evans -- Health care, personal assistance and assistive technology : are in-kind benefits key to independence or dependence for people with disabilities? / Andrew I. Batavia.
Papers presented at a conference on disability, work, and cash benefits held December 8-10, 1994 in Santa Monica, California, jointly sponsored by National Academy of Social Insurance and the National Institute on Disability and Rehabilitation Research of the U.S. Department of Education.
Includes bibliographical references (pages 409-411) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: People with disabilities -- Employment -- United States -- Congresses; Disability insurance -- United States -- Congresses; Social security -- United States -- Congresses; Vocational rehabilitation -- United States -- Congresses; Sheltered workshops -- United States -- Congresses; Employee fringe benefits -- United States -- Congresses; Labor market -- United States -- Congresses; People with disabilities -- Employment -- Law and legislation -- United States -- Congresses; Personnes handicapées -- Travail -- États-Unis -- Congrès.; Assurance-invalidité -- États-Unis -- Congrès.; Sécurité sociale -- États-Unis -- Congrès.; Réadaptation professionnelle -- États-Unis -- Congrès.; Ateliers protégés -- États-Unis -- Congrès.; Avantages sociaux -- États-Unis -- Congrès.; Marché du travail -- États-Unis -- Congrès.; Personnes handicapées -- Travail -- Droit -- États-Unis -- Congrès.; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; Disability insurance; Employee fringe benefits; Labor market; People with disabilities -- Employment; People with disabilities -- Employment -- Law and legislation; Sheltered workshops; Social security; Vocational rehabilitation; United States; disability benefit; workers with disabilities; cash benefit; fringe benefit; vocational rehabilitation; work incentive; social cost; social policy; employment policy; employment opportunity; return to work; sheltered workshop; private sector; autonomy of people with disabilities; USA; Western Europe; prestations d'invalidité; travailleur handicapé; prestations en espèces.; avantages accessoires; réadaptation professionnelle; incitation au travail; coût social; politique sociale; politique de l'emploi.; possibilités d'emploi.; réinsertion professionnelle; atelier protégé; secteur privé; autonomie du handicapé; Etats-Unis.; Europe occidentale; prestaciones de invalidez